Evaluation of the impact of vegetable oils on the germination of lettuce seeds (Lactuca sativa L.) - Thode Filho, Sérgio; Jorge, Emanuele Nunes de Lima Figueiredo; Souza, Leonardo Corrêa de; Pereira, Matheus Lucas Rocha da Silva; Nascimento, Raiane de Almeida Marinho; Pereira, Ray da Siqueira; Franco, Heider Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Vegetable oils were widely used for food production at different levels: domestic, commercial or industrial. Due to the improper discharge of its remainings in the sewage system, they becom potentially polluting for water resources and can cause many problems to wastewater treatment plants operation, provoking efficiency loss and increasing operational costs. The objective of this work was to evaluate the impact of four vegetable oils (soy, corn, canola and sunflower) on germination and development of lettuce seeds (Lactuca sativa L.). The experimental design had 7 treatments for the test group (oils) and 1 control group. The control group was composed of 4 mL deionized water. At the end of 120 h (5 days), the following parameters were evaluated: number of germinated seeds and length of rootlets. It was verified a negative effect on the germination rate and root growth as a function of the increase of the doses. Starting the dose with 0.1 mL of oil, was observed inhibition in rate of germination and root growth. All the oils studied were equally impacting to the parameters of seed germination and root growth of lettuce seeds.